Thermoeconomic comparison between pure and mixture working fluids of organic Rankine cycles (ORCs) for low temperature waste heat recovery. (December 2015) - Feng, Yongqiang; Hung, TzuChen; Greg, Kowalski; Zhang, Yaning; Li, Bingxi; Yang, Jinfu
Highlights: Thermoeconomic comparisons between pure and mixture working fluids have been investigated. Four models are proposed for mixture working fluids. Model 2 is the favorable operation condition. The mixture working fluids present better exergy efficiency but worse LEC except model 1. Abstract: Based on the thermoeconomic multi-objective optimization, simultaneously considering exergy efficiency and levelized energy cost ( LEC ), the thermoeconomic comparisons between pure and mixture working fluids of organic Rankine cycles (ORCs) have been investigated. Four models are proposed based on the different location of evaporating bubble point temperature or condensing dew point temperature for mixture working fluids. The effects of mass fraction and four key parameters (evaporator temperature, condenser temperature, pinch point temperature difference and degree of superheat) on exergy efficiency and levelized energy cost ( LEC ) are examined. Pareto-optimal solutions of four models using 0.7R245fa/0.3R227ea are obtained and compared. Taking mass fraction into account, the thermoeconomic comparisons between pure and mixture working fluids have been studied. Research demonstrates that the mixtures don't always present better thermodynamic performance and economic performance than pure working fluids. Model 2 ( T 7 = T E, T 3 = T C ) is the favorable operation condition for its highest thermodynamic performance and relatively low economic factor. Taking mass fraction as decision variable, Pareto-optimal solutions for models 1, 2, 3 and 4 in pairs of (exergy efficiency (%), LEC (/kW h)) are (56.71, 0.188), (57.67, 0.192), (57.11, 0.194), and (56.91, 0.192), respectively. Compared with pure working fluids, the mixture working fluids present better exergy efficiency but worse LEC except model 1.